STRATEGI ADOPSI TEKNOLOGI KESEHATAN DIGITAL DI KLINIK PRATAMA DURI DENGAN PENDEKATAN TECHNOLOGY-ORGANIZATION-ENVIRONMENT (TOE) - Belman Junaidi; Adi Rahmat; Richa Afriana Munthe (Smart Education, 2026)
Abstrack: Belman Junaidi, Postgraduate School of Management, Lancang Kuning Univerisity. Digital Health Technology Adoption Strategy at Duri Primary Clinic Using TOE Approach. Supervisory Chairpeson Assoc. Prof. Dr. Adi Rahmat, S.E., M.M and Supervisory Member Dr. Richa Afriana Munthe, S.E., M.M.The purpose of this study was to determine the digital health technology adoption strategy at the Pratama Duri Clinic using the TOE Approach. Using the Technology-Organization-Environment (TOE) framework for health technology adoption strategies is to identify and analyze key factors that influence the success of technology implementation in the health system. This study uses a quantitative research type. The data collection technique uses a questionnaire. The sample in this study amounted to 61 employees of the Pratama Reza Medika Clinic, Pratama Khaira Clinic and Pratama Mandau Sejahtera Clinic. This study used Partial Least Squares (PLS) data analysis. The results of the study indicate that digital health technology has a significant influence through the TOE approach (Technology, Organization and Environment). Keywords: Strategy, Adoption, Digital Health, TOE Approach. Abstrak: Tujuan penelitian ini untuk mengetahui strategi adopsi teknologi kesehatan digital di Klinik Pratama Duri dengan Pendekatan TOE. Menggunakan kerangka Technology-Organization-Environment (TOE) untuk strategi adopsi teknologi kesehatan adalah mengidentifikasi dan menganalisis faktor-faktor kunci yang memengaruhi keberhasilan implementasi teknologi dalam sistem kesehatan. Penelitian ini menggunakan jenis penelitian kuantitatif. Teknik pengumpulan data menggunakan kuisioner. Sampel dalam penelitian ini berjumlah 61 orang karyawan Klinik Pratama Reza Medika, Klinik Pratama Khaira dan Klinik Pratama Mandau Sejahtera. Penelitian ini menggunakan analisa data Partial Least Squares (PLS). Hasil penelitian menunjukkan bahwa teknologi kesehatan digital berpengaruh signifikan melalui pendekatan TOE (Teknologi, Organisasi dan Lingkungan). Kata Kunci: Strategi, Adopsi, Kesehatan Digital, Pendekatan TOE.